PELATIHAN KOMUNIKASI TERAPEUTIK GUNA MENINGKATKAN PENGETAHUAN PERAWAT DALAM CARING - Rika Sarfika; Esthika Ariany Maisa; Siti Yuliharni; Dewi Eka Putri; Ira Erwina; Bunga Permata Wenny; Rika Fatmadona; Dwi Novrianda (LPPM Universitas Andalas, 2020)
The caring behavior is the main basis that underlies the mutual help relationship established between the nurse-patient. This therapeutic relationship is built through therapeutic communication that is practiced to achieve the success of the therapeutic program. However, there are still many nurses who do not apply therapeutic communication in interacting with patients. This activity was aimed to improve nurses' understanding through therapeutic communication training for nurses at a hospital in Padang city. The implementation of this activity used method lecture, discussion, and demonstration. Learning was carried out for 8 hours effectively, before and following learning the measurement of pre-test and post-test knowledge were carried out. The number of participants as many as 20 nurses who served in the unit inpatient care room. Based on paired t-test, the results obtained were differences in the average knowledge of participants about therapeutic communication before and after training (p value = 0,000). The average difference in knowledge scores before and after training was 2.550. The results of this activity showed that learning activities using lecture, discussion, and demonstration methods were proven to increase nurses' knowledge about therapeutic communication. Therefore, it is suggested that this activity can be carried out routinely in order to improve the quality of nursing care for patients through the application of good therapeutic communication by nurses.